Decreasing water concentration in the Uragan-3M device with UHF discharge - Kozulya, M.M.; Korovin, V.B.; Lozin, A.V.; Krasyuk, A.Yu.; Mironov, Yu.K.; Romanov, V.S.; Shtan, A.F.; Solodovchenko, S.I.; Baron, D.I.; Shapoval, A.N.; Chernyshenko, V.Ya.; Pashnev, V.K. (Вопросы атомной науки и техники, 2014)
Uragan-3M device vacuum chamber is a cylinder with volume of 70 m³. Between the operation series, it is opened to the atmosphere for scientific and technical works. The problem of high water vapour concentration in the residual gas appears each time the chamber is closed and pumped. Effective water vapour removal can be achieved by baking the vacuum chamber walls at high temperatures (200…400°C) or increasing atomic hydrogen flow produced by the wall conditioning discharge in the plasma confining volume, as far as Н₂О detachment speed should be higher than adhesion. It's not technically possible to heat Uragan-3M device vacuum chamber. Room temperature of the vacuum chamber walls is not an obstacle for an UHF discharge with high enough plasma density (8∙10¹⁰ cm⁻³). Вакуумная камера установки Ураган-3М представляет собой цилиндр из нержавеющей стали объемом ~70 м³. Периодически вакуумная камера вскрывается для напуска атмосферного давления с целью проведения научных и технических работ. После ее закрытия и откачки до высокого вакуума, появляется проблема, связанная с высокой концентрацией воды в остаточном газе. Для эффективного удаления паров воды обычно используется прогрев стенок камеры при температуре 200…400°С. Альтернативой является поддержание плазменного разряда в водороде, обеспечивающего поток атомарного водорода на стенку. На установке Ураган-3М прогрев камеры технически не возможен, поэтому использовался плазменный СВЧ-разряд с достаточной величиной плотности плазмы (8∙10¹⁰ см⁻³). Вакуумна камера установки Ураган-3М являє собою циліндр з нержавіючої сталі об'ємом ~70 м³. Періодично вакуумна камера відкривається для напуску атмосферного тиску для проведення наукових і технічних робіт. Після її закриття та відкачування з'являється проблема, пов'язана з високою концентрацією води в залишковому газі. Для ефективного видалення парів води необхідно підтримувати стінки камери при високій температурі (200…400°С). Альтернативою є підтримка плазмового розряду у водні, що забезпечує потік атомарного водню на стінку. На установці Ураган-3М прогрів камери технічно не можливий, тому кімнатну температуру стінок камери доводиться компенсувати достатньою величиною щільності плазми (8∙10¹⁰ см⁻³) НВЧ-розряду.